Analisis Hukum Perdata terhadap Perubahan dan Penambahan Nama pada Seseorang - Utomo, Abdulah Rafi (Proceedings Series on Social Sciences & Humanities, 2024)
Civil law analysis of changes and additions to a person's name This study refers to the civil law analysis of changes and additions to a person's name. This study uses a standard legal approach with descriptive research methods and qualitative analysis. The data used are secondary data obtained through bibliographic and documentary research. The results of the study indicate that changes and additions to a person's name can be done with procedures in accordance with civil law. Name changes can be done by submitting a name change application to the court and following the established procedures. Additions to a name can be done by submitting a name addition application to the court and following the established procedures. The conclusion of this study is that changes or additions to a person's name can be done according to procedures in accordance with civil law. Hopefully this study can contribute to the development of civil law and provide useful information for the community.